Block Course Learning Approach in Thailand: Prospective Mathematics Teachers’ Perceptions - Nabila Firda Rahmalia (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is driven by the limited literature regarding the effectiveness of the block course learning model in mathematics teacher education, particularly in Thailand's international school context. While this model is known for its intensity, understanding of how prospective teachers perceive its practical implementation remains scarce. This study aims to describe the perceptions and experiences of the researcher as a prospective mathematics teacher regarding block course implementation at Yanyawit School, Thailand, with student learning outcomes as supporting evidence. A qualitative-dominant mixed-methods approach with a Sequential Exploratory design was employed. The qualitative phase explored pedagogical phenomena to provide a framework for the subsequent descriptive quantitative phase. The unit of analysis focused on the researcher's own experiences as a student teacher, supported by interviews with the deputy principal, mathematics teachers, and 29 MathayomTon 1 students selected via purposive sampling. Data were collected through participant observations during the internship period, semi-structured interviews, and mathematics final examination (UAS) documents validated by expert review. Qualitative thematic analysis revealed four emergent themes: 1) Institutional strategic rationale for curriculum integration, 2) Pedagogical strategies using mathematical play media, 3) Implementation barriers related to student fatigue during long sessions (60-120 minutes), and 4) Positive perceptions of academic impact. Descriptive statistical analysis of exam scores supported these findings, showing that the majority of students achieved moderate outcomes (60-79). Future research is recommended to conduct correlation tests between block course time intensity and conceptual retention, while developing diverse active teaching methods to mitigate learning fatigue during extended instructional durations.